Analysis Value of The Official Trailer of Film “The Santri” in Living Hadith Perspective - Kholidun Kholidun; Lilik Channa (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
This study intends to observe moral values in the Official Trailer of the Film